Evaluation of pathogenicity of Botrytis species isolated from different legumes - Brauna-Morževska, Elīna; Stoddard, Frederick L.; Bankina, Biruta; Kaņeps, Jānis; Bimšteine, Gunita; Petrova, Irina; Neusa-Luca, Ingrīda; Roga, Ance; Fridmanis, Dāvids (Frontiers in Plant Science, 2023)
Fungi of genus Botrytis are important pathogens of legumes, causing gray mould and chocolate spot diseases. The use of molecular methods to identify pathogens has resulted in the discovery of several new Botrytis species and new associations of pathogens with diseases. Thus, chocolate spot of faba bean is now associated with at least four species: B. fabae, B. cinerea, B. pseudocinerea and B. fabiopsis. Species of Botrytis differ in host plant, pathogenicity, fungicide resistance and other relevant properties that affect disease control. The aim of this study was to evaluate the in vitro virulence of Botrytis spp., isolated from different legume crops. Between 2014 and 2019, 278 isolates of Botrytis were obtained from infected legumes in Latvia. A phylogenetic analysis was carried out by sequencing three nuclear genes, RPB2, HSP60, and G3PDH. A set of 21 representative isolates was selected for pathogenicity tests on detached leaves of faba bean, field pea, lupin and soybean using 5-mm mycelium-agar plugs. The diameter of the formed lesions under the inoculated plug was measured crosswise each day. The datasets were subjected to analysis of variance with the split-plot design of the experiment and repeated-measures model. Six species were identified: B. cinerea, B. fabae, B. pseudocinerea, B. fabiopsis, B. euroamericana and B. medusae. Naturally occurring infections of B. fabiopsis were found on chickpea, B. euroamericana on faba bean and B. medusae in lupin seeds. Species and isolate had significant effect on pathogenicity on all crops tested. Several isolates were pathogenic on two or more host species: two of B. pseudocinerea, two of B. cinerea, two of B. fabiopsis and the one of B. medusae. One isolate of B. pseudocinerea and two of B. fabiopsis caused primary lesions on all five host species. The results show that these Botrytis species have a broad host range that should be borne in mind when planning crop sequences and rotations.